Has the mental health and wellbeing of teachers in England changed over time? New evidence from three datasets. (2nd November 2021) - Jerrim, John; Sims, Sam; Taylor, Hannah; Allen, Rebecca
ABSTRACT: This paper presents the first empirical evidence on long-run trends in teacher mental health and wellbeing in England. We find that, although there has been a recent rise in mental health problems reported by teachers in England, this is mirrored by workers in other professions – with little evidence of a simultaneous change in levels of personal wellbeing. Our conclusion is therefore that the mental health and personal wellbeing of teachers in England has remained broadly stable over the last 20 years, though this group may be more likely to report such problems now than previously.